1988
DOI: 10.1161/01.res.62.6.1065
|View full text |Cite
|
Sign up to set email alerts
|

Rates of glycolysis and glycogenolysis during ischemia in glucose-insulin-potassium-treated perfused hearts: A 13C, 31P nuclear magnetic resonance study.

Abstract: The effects of 11.7 mM glucose, insulin, and potassium (GIK) on metabolism during ischemia were investigated in the perfused guinea pig heart using magnetic resonance spectroscopy. Intracellular metabolites, primarily glycogen and glutamate, were labeled with I3 C by addition of [l-13 C]glucose to the perfusate during a normoxk, preischemic period. 13C and 31 P NMR spectroscopy was used to observe the metabolism of "C-labeled metabolites simultaneously with high-energy phosphorus metabolites and pH. The ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

1989
1989
1993
1993

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…10 Ml of 1251-ICYP (20 pM final concentration) were incubated at 37°C for 30 min in the presence of varying concentrations of (-)-isoproterenol (10 nM to 100MM) after the reaction was initiated by the addition of80…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…10 Ml of 1251-ICYP (20 pM final concentration) were incubated at 37°C for 30 min in the presence of varying concentrations of (-)-isoproterenol (10 nM to 100MM) after the reaction was initiated by the addition of80…”
Section: Methodsmentioning
confidence: 99%
“…Subsequent studies into the beneficial mechanism of GIK indicated that glucose reduced the use of free fatty acids thereby decreasing myocardial oxygen consumption and retarding progressive myocardial injury (9). Nuclear magnetic resonance studies suggest that exogenously supplied glucose may supplement endogenous glycogen mobilization, delay glycogen depletion and prolong the production ofhigh energy phosphates required by myocardial cell metabolism (10).…”
Section: Introductionmentioning
confidence: 99%
“…Both measurements are difficult in reperfused myocardium where isotopic and metabolic steady state are difficult to establish. '3C is a stable isotope that has recently been applied to numerous problems in intermediary metabolism (33)(34)(35). '3C isotopomer analysis offers advantages over other measurements of substrate selection because it is technically simple, and anaplerosis and competition among several substrates can be assessed in a single experiment (36)(37)(38).…”
Section: Introductionmentioning
confidence: 99%
“…It might be effective if the dosage of insulin was increased or insulin was given for a longer period. Another possible reason is that during the 30-min hypoperfusion with NE, severe changes in the myocardium might occur in our preparations as shown in non diabetic hearts (23) in which the significant decrease in high energy phosphate and the elevation in intracellular pH were observed during 15-min no-flow. Thus, these pos sibilities might injure the activities of enzymes that are associated with energy metabolism and/or myocardial ion homeostasis, resulting in insufficient restoration by post-treated insulin.…”
Section: Animals and Treatmentmentioning
confidence: 90%